Micronutrients and omega-3 PUFAs to promote healthy ageing: informing a physiology-based complementation strategy - Mette M. Berger; Renée Blaauw; Patrizia D’Amelio; Nicole Ehrhart; Adrian F. Gombart; Leah Gramlich; Reto W. Kressig; Philip C. Calder (GeroScience, 2026)
Global population ageing is increasing the burden of chronic disease, functional decline, and loss of independence. For most organs, decline in function starts during the 5th decade of life. Micronutrient (MN) insufficiencies/deficiencies are common and may accelerate biological ageing. MNs are required to support multiple physiologic processes, including mitochondrial homeostasis. Age-related declines in organ function are tightly linked to mitochondrial dysfunction, oxidative stress, inflammageing, and immunosenescence. Selected MNs (vitamins B, C, D, E, iron, selenium, zinc) are critical cofactors for mitochondrial function, antioxidant defence, immunity, and resolution of inflammation. Inadequate MN intakes require specific repletion strategies beyond diet for correction. Low intake, (patho)physiological changes, and common medications jointly contribute to compromised MN status. Emerging trials suggest that correcting MN deficiency may restore mitochondrial function and thereby promote healthy ageing. Optimizing intake over the lifespan represents another means to support healthy ageing. Nevertheless, MNs do not work individually but as a web, and may behave differently in different individuals. Further, low status of the n-3 polyunsaturated fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) is common in older adults, which favours inflammation and functional decline. EPA+DHA work in combination with MNs on inflammation containment. Routine risk assessment, selected biomarker measurement from midlife onwards, and well-designed trials are needed to complement an insufficient status. MN and EPA+DHA optimization should be integral to healthy ageing strategies.